Role of irrigation scheduling, puddling intensity and source of nutrients on yield of rice (Oryza sativa ) and its residual effect on succeeding wheat under irrigated agro-ecosystems of Jammu - SHARMA, ROHIT; KACHROO, DILEEP; BHARAT, RAJEEV; THAKUR, N P; KOUR, MANPREET (Journal of Soil and Water Conservation, 2022)
A field experiment was conducted during kharif 2005-06 and 2006-07 at Agronomy Research Farm, SKUAST-J, Main Campus, Chatha, Jammu to evaluate the effect of different levels of puddling intensity, irrigation scheduling and sources of nutrients on yield of rice and its residual effects on succeeding wheat crop. Puddling 3 times along with irrigation scheduled at soil matric potential (SMP) 150 cm suction coupled with application of vermicompost @ 6t ha-1 resulted in significant increase in paddy grain and straw yield, number of tillers per m-2, grain weight panicle-1, 1000- grain weight. Water expense was maximum(101.29 cm and 132.36 cm) where irrigation was applied at 2 Days after disappearance of ponded water (DADPW) during both the years, while Water Expense Efficiency (WEE) was higher (61.45 kg ha-1cm-1) at irrigation scheduling at SMP at 150 cm suction rather than irrigation at 2 and 4 DADPW during both the years. However, among nutrient sources application of inorganic fertilizer showed maximum water expense of 81.5cm and 118.16cm during both the years with WEE of 53.54 kg ha-1cm-1 in first year but in 2nd year WEE was recorded higher (39.05 kg ha-1cm-1) in vermicompost application @ 6t ha-1. Puddling 3 times in rice also showed higher WEE as compared to normal practice and 2 times puddling . Nutrient (NPK) availability to rice crop was significantly more when nutrient source like vermicompost, FYM+Inorganic applied with irrigation scheduling at SPM at 150 cm suction. However, level of puddling and irrigation schedule had no residual effect on wheat yield but the vermicompost as nutrient sources had significant residual effect on grain and straw yield of succeeding wheat crop. Irrigation schedulingbased on SMP at 150 suction recorded maximum Net Return of Rs 33816 in first year with B:C ratio of 2.61 and 2.91 in 1st and 2nd year respectively. However application of vermicompost @ 6t ha-1 recorded maximum net return of R 37499 in 2nd year of study.